Migrant Workers’ Vulnerabilities to Exposure of Violent Extremism: Case Study of Indonesian Returnee Women Migrant Workers in Hong Kong - Aris Arif Mundayat; Wahyu Susilo; Zulyani Evi (Yayasan Jurnal Perempuan, 2020)
This qualitative study analyzes the involvement of female perpetrators of extreme violence acts and suicide bombings against the modern state as a symbol of their religious enemies. The topic is crucial as it shows the meaningful reasons for female militancy, where women are seen to exceed their gender norms. It is not because they take their own lives but also to bring their children to embrace death in the process of religious-based violent extremism. This article opposes the idea of gender in binary opposition as female and male, but rather see it as a range of gender spectrum. The understanding of the main symbolic structures here is crucial as it is capable of dismantling aspects that temporarily limit gender roles. At the same time, what they are doing is constructing new ideas that “God do not see you in someone appearance” included their gender, but rather their “action”. It is their way to find justification to support extreme violence, although it is against religious teaching.